Health Literacy and Healthcare in Cancer Screening (Turkey Health Literacy Journal, 2022)
It is an undeniable fact that the concept of health literacy, which is valid at all levels in the field of health, contributes to the complete well-being of people. In 1974, WHO defined health literacy as “all the skills of an individual to reach, understand and use health information in order to maintain health and maintain a healthy state so that individuals can live a healthy life” (1,2). All steps, from primary health care services to tertiary and palliative services, can be fed from health literacy. For this reason, low or insufficient level of health literacy can negatively affect the health system. One of the components of primary health care services is preventive health services. In the absence and/or presence of risk factors, all services such as early detection and early treatment of diseases are called preventive health services. Cancer screening is one of the most important preventive health services. Although cancers have high mortality and morbidity levels, it is also possible to identify them early. For this reason, cancer screening programs are important in terms of both individual and social health. Insufficient level of health literacy also causes disruptions in preventive health services. The fact that individuals with insufficient health literacy level apply to cancer screening programs at a lower rate brings about negative consequences in terms of both individual health, social health and cost in social health.